(untitled) (Ustozlar uchun, 2025)
The integration of interactive games and mobile applications into English language teaching transforms traditional lessons into dynamic, engaging, and learner-centered experiences. These digital tools enhance motivation, enable individualized learning, develop communication skills, and create a meaningful environment where language is acquired naturally through practice and play.